Adherence to Mediterranean diet among Lithuanian and Croatian students during COVID-19 pandemic and its health behavior correlates - Mieziene, Brigita; Burkaite, Greta; Emeljanovas, Arunas; Tilindiene, Ilona; Novak, Dario; Kawachi, Ichiro (Frontiers in Public Health, 2022)
Maintaining healthy behavior, especially in times of crisis like the COVID-19 pandemic is particularly important for staying healthy. Nutrition is an everyday behavior and along with other health-related behaviors is associated with many health outcomes. This study aimed to assess and compare adherence to the Mediterranean diet (MedDiet) and particular food choices among the Mediterranean and non-Mediterranean populations of university students and identify its lifestyle correlates at the outburst of the COVID-19 pandemic. In total self-reported data on health-related behavior, and sociodemographic characteristics were collected from 1388 study participants 66.4% were Lithuanians, and 33.6% were Croatians. Results revealed that vegetables, olive oil, fruits, nuts, legumes, and fish were remarkably under-consumed among university students in the Mediterranean and non-Mediterranean countries during the COVID-19 pandemic and the composite diet is similar between countries. The higher adherence to MedDiet is associated with physical activity (β=.15) and non-smoking (β=.08). In times of crisis, public health entities should provide knowledge, skills, and tools for healthy nutrition specifying them by age and sub-population. Interventions at the university should be implemented to build infrastructure and provide an access to health behavior-friendly environments.